ChemInform Abstract: Controlling Regiochemistry in the Gold‐Catalyzed Synthesis of Unsaturated Spiroketals. Issue 14 (April 2015) - Paioti, Paulo H. S.; Ketcham, John M.; Aponick, Aaron
Abstract: The problematic regiochemical issues in the metal‐catalyzed spiroketalization of alkynes are addressed by utilizing an acetonide as a regioselectivity regulator in the production of monounsaturated spiroketals.